2022
DOI: 10.3390/nu14214547
|View full text |Cite
|
Sign up to set email alerts
|

Resistant Starch as a Dietary Intervention to Limit the Progression of Diabetic Kidney Disease

Abstract: Diabetes is the leading cause of kidney disease, and as the number of individuals with diabetes increases there is a concomitant increase in the prevalence of diabetic kidney disease (DKD). Diabetes contributes to the development of DKD through a number of pathways, including inflammation, oxidative stress, and the gut-kidney axis, which may be amenable to dietary therapy. Resistant starch (RS) is a dietary fibre that alters the gut microbial consortium, leading to an increase in the microbial production of sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 149 publications
0
4
0
Order By: Relevance
“…Previous studies have revealed that the supplementation of dietary fiber reduced serum levels of uremic toxins and proinflammatory cytokines, and reversed kidney injuries in CKD (Chiavaroli et al, 2015;Felizardo et al, 2019;Zhong et al, 2021). Similarly, recent studies indicated that dietary fiber ameliorates diabetes-related dysbiosis and protect against DKD through promoting SCFA-producing bacteria, which are able to attenuate inflammatory and oxidative stress (Drake et al, 2022;Li et al, 2020;Lv et al, 2022).…”
Section: Dietmentioning
confidence: 98%
“…Previous studies have revealed that the supplementation of dietary fiber reduced serum levels of uremic toxins and proinflammatory cytokines, and reversed kidney injuries in CKD (Chiavaroli et al, 2015;Felizardo et al, 2019;Zhong et al, 2021). Similarly, recent studies indicated that dietary fiber ameliorates diabetes-related dysbiosis and protect against DKD through promoting SCFA-producing bacteria, which are able to attenuate inflammatory and oxidative stress (Drake et al, 2022;Li et al, 2020;Lv et al, 2022).…”
Section: Dietmentioning
confidence: 98%
“…In addition, lifestyle intervention, such as dietotherapy and exercise training, is also a common strategy for DN therapy. Dietary fiber was proved to attenuate the progression of DN by promoting the expansion of SCFAs-producing bacteria, such as Prevotella and Bifidobacterium , which can inhibit inflammation and oxidative stress ( Li Y. J. et al, 2020 ; Drake et al, 2022 ). In STZ-induced DN rats, Mulberry leaf tea markedly ameliorated hyperglycemia and renal injury by restoring the abundance of Adlercreutzia , Anaerofustis , Coprococcus , Dorea , Roseburia , Oscillospira , Phascolarctobacterium , Coprobacillus , Sutterella and RF39 , which indicated that Mulberry leaf tea can be used as a dietotherapy for DN therapy through gut–kidney axis ( Sheng et al, 2018 ).…”
Section: Gut Microbiota-targeted Dn Therapiesmentioning
confidence: 99%
“…Senescence is largely promoted by the chronic low-grade inflammation that is a feature of prediabetes [117]. In this context, prediabetic people frequently have elevated levels of various inflammatory mediators, including interleukin-1 beta (IL-1β), interleukin-18 (IL-18), and high-sensitivity C-reactive protein (hs-CRP) [131]. The systemic inflammation that accelerates aging is largely caused by these inflammatory factors [132].…”
Section: Chronic Inflammation and Its Implications For Senescencementioning
confidence: 99%